DANOS E CONTROLE DO BICUDO NA PRODUÇÃO DE ALGODÃO EM CAROÇO - Scarpellini, José Roberto; Santos, José Carlos C.; Pretto, Denis (REVISTA DE AGRICULTURA, 2015)
DANOS E CONTROLE DO BICUDO NA PRODUÇÃO DE ALGODÃO EM CAROÇO